PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Suadnyani, Desak Made Lingga; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen, 2018)
The purpose of this study was to analyze the effect of transformational leadership, motivation and job satisfaction on organizational commitment at Wyndham Garden Hotels Kuta Village Badung Regency. Data type has been used in this study that are quantitative and qualitative. Data has been used in this study are primary that get directly through fill of questioner by respondents. Population in this study is all employee in Wyndham Garden Hotels Kuta Village Badung Regency by number of 108 people. From the result shows that transformational leadership have been positive and significant toward organizational commitment at Wyndham Garden Hotels Kuta Village Badung Regency. Motivation have been positive and significant toward organizational commitment at Wyndham Garden Hotels Kuta Village Badung Regency. Job satisfaction have been positive and significant toward organizational commitment at Wyndham Garden Hotels Kuta Village Badung Regency.   Keywords: transformational leadership, motivation, job satisfaction